Effect of NR3C2 genetic polymorphisms on the blood pressure response to enalapril treatment. (February 2014) - Luo, Jian-Quan; Wang, Lu-Yan; He, Fa-Zhong; Sun, Ning-Ling; Tang, Gen-Fu; Wen, Jia-Gen; Luo, Zhi-Ying; Liu, Zhao-Qian; Zhou, Hong-Hao; Chen, Xiao-Ping; Zhang, Wei
Aim: The mineralocorticoid receptor (MR; also known as NR3C2) plays important roles in the modulation of blood pressure. The effect of NR3C2 polymorphisms on antihypertensive response to enalapril was investigated.Patients & methods: Two hundred and seventy nine essential hypertension patients treated with enalapril were genotyped for two NR3C2 tagSNPs, rs5522 and rs2070950, by Sequenom MassArray™ technology.Results: The reductions in diastolic blood pressure (DBP) were significantly greater in AA homozygotes compared with AG+GG genotype carriers for the rs5522 polymorphism (p = 0.009), and the reductions in DBP were greater in GG homozygotes compared with GC+CC genotype carriers for the rs2070950 polymorphism, with marginal significance (p = 0.065). Stepwise multiple regression analysis indicated that significant predictors of DBP reduction were baseline DBP (p < 0.001), waist:hip ratio (p = 0.001) and rs5522 genotype (p = 0.003).Conclusion: NR3C2 rs5522 affects blood pressure response to enalapril treatment and may serve as a useful pharmacogenomic marker of antihypertensive response to enalapril in essential hypertension patients. Original submitted 8 August 2013; Revision submitted 29 August 2013; Published online 23 September 2013